High diversity of Cladocera (Crustacea: Branchiopoda) in a Ramsar site Lake Kud-Thing, Northeast Thailand - Tiang-Nga, Supatra; Sinev, Artem Y.; Sanoamuang, La-Orsri (Zootaxa, 2020)
An intensive study of cladoceran diversity in Lake Kud-Thing, a Ramsar site of Bueng Kan Province, Thailand, was conducted. One hundred and twenty-five qualitative samples were collected from 15 localities during the period from June 2012 to November 2014. A total of 58 species belonging to 38 genera was recorded. Three species, Chydorus idrisi Sinev 2014, Karualona kwangsiensis (Chiang 1963) and Streblocerus cf. serricaudatus (Fisher 1849) are new records for Thailand. The most species rich family was Chydoridae (32 species, 55% of the encountered species in the lake) followed by Sididae (8 species, 14%) and Macrothricidae (8 species, 14%) while only a single species of Ilyocryptidae was observed. The most frequently encountered planktonic species were Ceriodaphnia cornuta Sars 1885, Bosmina cf. meridionalis Sars 1904 and Ephemeroporus barroisi (Richard 1894). A newly described chydorid, Anthalona spinifera Tiang-nga, Sinev & Sanoamuang 2016, was also recorded from this lake. The number of cladocerans recorded in this study is remarkably higher than that of previous studies in other natural lakes (17–40 species) within Thailand. In addition to earlier records, the number of cladocerans of Lake Kud-Thing has been updated to 62 species, about two times higher than that of other lakes in this region. Thus, our results suggest that Lake Kud-Thing is one of the biodiversity hotspots for Cladocera of Southeast Asia.